2011
DOI: 10.1002/bit.23285
|View full text |Cite
|
Sign up to set email alerts
|

Optically controlled contraction of photosensitive skeletal muscle cells

Abstract: As the skeletal muscle cell is an efficient force transducer, it has been incorporated in bio-microdevices using electrical field stimulation for generating contractile patterns. To improve both the spatial and temporal resolutions, we made photosensitive skeletal muscle cells from murine C2C12 myoblasts, which express channelrhodopsin-2 (ChR2), one of archaea-type rhodopsins derived from green algae Chlamydomonas reinhardtii. The cloned ChR2-expressing C2C12 myoblasts were made and fused with untransfected C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
(29 reference statements)
2
40
0
1
Order By: Relevance
“…Previous work showed that ChR2 enables temporally precise (tens of milliseconds) and spatially confined control of cardiac muscle contraction (17). A recent work reported the feasibility of optical control for skeletal muscle contractions (40). Here, we extend the results of this work by demonstrating selective activation of individual myotubes with confined illumination as well as formation, characterization and optical control of genetically engineered, 3D skeletal muscle microtissues.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that ChR2 enables temporally precise (tens of milliseconds) and spatially confined control of cardiac muscle contraction (17). A recent work reported the feasibility of optical control for skeletal muscle contractions (40). Here, we extend the results of this work by demonstrating selective activation of individual myotubes with confined illumination as well as formation, characterization and optical control of genetically engineered, 3D skeletal muscle microtissues.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ChR2 has been expressed in neurons (19) to monitor and control their membrane potential, intracellular acidity, Ca 2+ influx, and other cellular processes (see ref (14) for review). In addition, ChR2 has been used to manipulate the membrane excitability of cardiomyocytes (20)(21)(22), skeletal muscle cells (23) and cell lines expressing voltage-gated ion channels (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Pulsatile electrical stimulation can also be used to induce and pace the muscle cells38. Recently, light-induced stimulation of genetically-engineered muscle cells that express the light-activated cation channels, halorhodopsin or channelrhodopsin-2 was demonstrated39404142. Integration of these engineered muscle cells to optically drive the bio-bots offers another exciting future possibility.…”
Section: Discussionmentioning
confidence: 99%